Mammalian dental diversity: an evolutionary template for regenerative dentistry - Popowics, Tracy; Mulimani, Priti (Frontiers in Dental Medicine, 2023)
The discovery of odontogenic mechanisms essential for regenerating dental tissues and eventually developing a biomimetic artificial whole tooth for replacement is an ongoing aspiration for dental clinicians and researchers. Studying the diversity, development and evolutionary changes of mammalian dentitions can provide key insights into the mechanisms of odontogenesis that can be harnessed for regenerative dental medicine. A myriad of influences is expected to have shaped the dentitions of mammals and our objective is to highlight the contributions of phylogeny, functional adaptation, and development to tooth shape. Innovations in tooth shape analysis will be discussed, such as in imaging methodologies and quantitative comparisons, molecular biology approaches to phylogeny and the ontogenetic basis of tooth form. Study of the inter- and intra-species differences in tooth form as well as dental anomalies has provided clues toward the mechanisms of evolutionary change in dental form. Thus, phenotypic variation in tooth shape will also be discussed, including the role of development in creating tooth shape differences that evolutionary selection pressures may act upon. Functional adaptations have occurred in the context of the phylogenetic signal of primitive mammals, and predecessors to each phylogenetic branch, and examples will be discussed within members of the Order Carnivora, the Superfamily Suoidea and the Order Primates. The comparative study of mammalian tooth shape holds the potential to inform dental research areas, such as etiopathogeneses of dental variation and tooth shape anomalies, molecular mechanisms of tooth development and functional issues. Ultimately, insights from these research areas can be potentially translated for futuristic clinical applications like regeneration of various tooth tissue layers and eventually full tooth replacement.